Diagnosis of the physical strain at the truck operator's workstation - Kowalczyk, Anna; Chodoła, Izabela; Kulczycka, Kinga; Stychno, Ewa (Journal of Education, Health and Sport, 2018)
The occupation of a truck driver may involve excessive physical effort, long hours of sitting in a forced posture (uncomfortable seat) and exposure to prolonged general vibrations. As a result of this type of occupational exposure, pain in the musculoskeletal system may develop over a shorter or longer period of time. In order to counteract the adverse effects of strenuous physical activity, it is recommended to measure and reduce it to a safe level, as recommended by physiologists and ergonomists. The aim of this study is to assess the physical strain on the stand of a truck operator according to the Lehmann method.